Synchronous arterial resections in pancreatic cancer – still a matter of debate?. Issue 2 (February 2021) - Barreto, Savio George; Kleeff, Jorg
Abstract: Surgery remains the cornerstone of a multimodality approach aimed at cure in pancreatic cancer (PC). To improve outcomes in PC and widen the indications for surgical resection, surgeons have targeted borderline-resectable (BR) and locally advanced (LA) tumours having demonstrated the feasibility of synchronous arterial (SAR) and venous resections (SVR). However, the true benefit of SARs in PC in terms of improving overall survival has not been fully realised. One of the reasons for this lies in the fact that once the tumour involves the artery, it has already spread along the perineural autonomic plexus that surround it, resulting in early extended local and distant cancer dissemination. Thus, before advocating for the performance of routine SARs in PC, it is important to critically analyse the evidence and develop a structured framework to test if these operations truly hold a beacon of hope for patients with LAPC.